REVIEW OF THE RESULTS OF THYROID TUMOR SURGERY AT CUA DONG GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Background: Review of results of thyroid tumor surgery at Cua Dong General Hospital in 2022 - 2023.Objective: 115 patients were diagnosed with benign or malignant thyroid tumors, indicated for surgery and underwent surgery at the Department of Surgery, Cua Dong General Hospital from January 2022 to October 2023.Method: Cross-sectional study.Results: The average age of the research group was 36.48 ± 13.55 years old, with more women than men, the female/male ratio was 8.6/1. The main reasons for hospitalization were health check-ups (43.5%) and the discovery of a large mass in the neck (26.1%). Benign tumors accounted for 54.8% and were often mononuclear tumors (60.9%). Open surgery was the main treatment for thyroid tumors, while endoscopic surgery was only performed for benign tumors. The surgery time was mainly under 90 minutes (87%). Very few complications occurred during surgery (3.5%). The hospital stay was mainly from 3 to 7 days. The main postoperative complications were temporary hypocalcemia and temporary hoarseness. 79.1% of the surgical results were good.Conclusion: The surgery time was mainly under 90 minutes, surgical complications accounted for only 3.5%, postoperative complications were mainly temporary hoarseness and hypocalcemia, overall postoperative results: good accounted for 79.1%, average 20.69%.
Keywords: Thyroid tumor, thyroid surgery, complications.